Effect of Mantra Therapy on Feto-Maternal Wellbeing: A Systematic Review - Chouhan, Preeti; Garg, Ayush Kumar; Singh, B. M.; Suman, Sunita (Journal of Neonatal Surgery, 2025)
enhance psychological and physiological health. Feto-maternal wellbeing encompasses maternal emotional stability, endocrine balance, immunological competence, and fetal neurodevelopment. Elevated stress and anxiety during pregnancy can perturb hormonal homeostasis, particularly by increasing cortisol levels, and thereby negatively influence pregnancy outcomes. Owing to the rising interest in non-pharmacological prenatal interventions, mantra therapy has been increasingly advocated as a potential integrative and holistic strategy for maternal care. Objective: The present review seeks to investigate the influence of mantra therapy on feto-maternal health, with particular emphasis on its neurophysiological, psychological, and immunomodulatory roles throughout gestation. Additionally, it aims to identify methodological limitations in the current literature and underscores the necessity for rigorously designed empirical investigations. Methodology: This systematic review was performed under the PRISMA guidelines. Electronic databases, including PubMed, Scopus, Web of Science, Cochrane Library, and Embase, were systematically queried for peer-reviewed articles published between 2000 and 2024, employing pre-defined MeSH terminology and keyword combinations. Studies were included based on their focus on pregnant individuals receiving structured mantra-based interventions. Results: 12 studies met the inclusion criteria. These comprised randomized controlled trials (n=3), observational or interventional studies (n=6), theoretical models (n=2), and one systematic review. Across studies, mantra therapy, often integrated with meditation or yoga, was associated with reduced systolic blood pressure, improved sleep quality, lower anxiety levels, and decreased cortisol concentrations. Fetal auditory receptivity and potential immune modulation were also observed. Conclusion: While mantra therapy holds promising theoretical value in promoting feto-maternal health, its clinical applicability remains under-explored due to a paucity of biomarker-based studies. Therefore, future research should prioritize robust randomized controlled trials incorporating physiological and molecular indicators to validate their therapeutic efficacy